In vitro Studies of Antimicrobial Activity of Crude Extracts of the Indian Grasses Dhaman (Cenchrus ciliaris) and Kala-Dhaman (Cenchrus setigerus) - Singariya, Premlata (Medknow Publications & Media Pvt Ltd, 2012)
The aim of present study was to investigate the antimicrobial activity of Cenchrus ciliaris and Cenchrus setigerus extracts in order to use it as a possible source for new antimicrobial substances against important human pathogens. Crude extracts of the stem of Cenchrus ciliaris and Cenchrus setigerus were evaluated against some medically important pathogens viz. Escherichia coli, Raoultella planticola, Staphylococcus aureus, Pseudomonas aeruginosa, Bacillus subtilis, Enterobacter aerogenes, Candida albicans and Aspergillus flavus. The dried and powdered stems were successively extracted with hexane, toluene, isopropyl alcohol, acetone and ethanol using soxhlet assembly. The antimicrobial activity assay was done by both disc diffusion and serial dilution methods. Isopropyl alcohol extract of Cenchrus setigerus showed highest activity against Escherichia coli. The test pathogens were more sensitive to the isopropyl alcohol, acetone and ethanol extracts than to the hexane and toluene extracts except against Bacillus subtilis. Result reveals that the most bioactive compound was cycloleucolenol-9,19-cycloergost-24 (28)-en-3-ol, 4, 14-dimethyl acetate in both the species of Cenchrus grass, (19.15%) in isopropanol extract of Cenchrus setigerus whereas, (14.03%) in acetone extract of Cenchrus ciliaris.